Does higher education equip graduate students with the employability skills employers require? The perceptions of employers in Ghana - Damoah, O.B.O.; Peprah, A.A.; Brefo, K.O. (Taylor & Francis Group, 2021)
Recent changes in the labour market and higher education sector have placed graduates’ employability on the agenda of researchers, policy makers and employers in both advanced and developing economies. Yet, the question of whether higher education equips graduate students with the employability skills employers require remains under-studied particularly in a developing country like Ghana. Using survey data and employing a paired t-test analyses, our findings reveal that whilst the employers perceive graduate students to possess various critical skills which match industry demands, the graduate students fall short in these critical skills. The differences were statistically significant indicating that there are still gaps between what higher education is offering its students and what industry requires from graduates at the entry-level. Based on the findings, implications for theory, policy, and practice are discussed.
Research Article
Keywords: Employability skills; gap analysis; employers perception; Ghana